2015
DOI: 10.1038/ncomms9322
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the biotechnology potential of lactobacilli through comparative genomics of 213 strains and associated genera

Abstract: Lactobacilli are a diverse group of species that occupy diverse nutrient-rich niches associated with humans, animals, plants and food. They are used widely in biotechnology and food preservation, and are being explored as therapeutics. Exploiting lactobacilli has been complicated by metabolic diversity, unclear species identity and uncertain relationships between them and other commercially important lactic acid bacteria. The capacity for biotransformations catalysed by lactobacilli is an untapped biotechnolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
380
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(426 citation statements)
references
References 69 publications
18
380
0
9
Order By: Relevance
“…The phylogenetic relationships and taxonomy of the Lactobacillus genus have been complicated by this loss or replacement of large segments of their genomes. The most recent phylogenetic reconstruction revealed that Lactobacillus is paraphyletic and that 5 other genera are grouped within the lactobacilli as subclades (Sun et al 2014).…”
Section: Natural History Of the Genus Lactobacillusmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic relationships and taxonomy of the Lactobacillus genus have been complicated by this loss or replacement of large segments of their genomes. The most recent phylogenetic reconstruction revealed that Lactobacillus is paraphyletic and that 5 other genera are grouped within the lactobacilli as subclades (Sun et al 2014).…”
Section: Natural History Of the Genus Lactobacillusmentioning
confidence: 99%
“…Niche-specific genes have been identified in Lactobacillus species associated with dairy and gut environments (O'Sullivan et al 2009). On the other hand, the search for common niche-specific genetic loci for vaginal Lactobacillus species remains unresolved (Ravel et al 2011) despite their close phylogenetic relationships (Salvetti 2012;Sun et al 2014). …”
Section: Lactobacilli and Dental Caries Caries-specific Species Of Lamentioning
confidence: 99%
“…These lost genes, particularly related to cofactor biosynthesis and sporulation, are indicative of the shift to a more nutrient-rich environment (Makarova et al, 2006). Currently, it is known that Lactobacillus genome size varies from 1.23 Mb (L. sanfranciscensis) to 4.91 Mb (L. parakefiri) (Sun et al, 2015).…”
Section: Geneticsmentioning
confidence: 99%
“…WGS has provided invaluable insights into the genetics of starter cultures (2,3), and it is routinely used in epidemiology to identify outbreak-associated foodborne pathogens isolated from clinical samples, through comparison of the single-nucleotide polymorphism (SNP) profiles of outbreak strain genomes versus nonoutbreak strain genomes (4)(5)(6). Metagenomic sequencing enables elucidation of the roles of microorganisms during food production (7)(8)(9), and it can be used to track microorganisms of interest through the food production chain, as illustrated by Yang et al (10), who used whole-metagenome shotgun sequencing to track pathogenic species in the beef production chain.…”
mentioning
confidence: 99%